SISTEM PENDUKUNG KEPUTUSAN PENENTUAN JURUSAN SMA MENGGUNAKAN METODE SMART (STUDI KASUS: SMP ISLAMIYAH SAWANGAN) - Rarita Octaviani Sajallah; Dedin Fathudin (Universitas Lampung, 2026)
Abstract. In accordance with the partner school's new majoring policy effective from the 2026/2027 academic year, senior high school (SMA) major placement is now conducted in grade XI, shifting decision support systems at the junior high school (SMP) level from final decision-making to early recommendation. This study develops a web-based Decision Support System (DSS) using the Simple Multi Attribute Rating Technique (SMART) method to help students of SMP Islamiyah Sawangan obtain an objective preliminary major recommendation. The assessment uses two benefit-type criteria: Academic Interest (C1, 60%) and Academic Score (C2, 40%), with utility values normalized against three major alternatives (Science, Social Studies, and Language). The system was built using PHP, MySQL, and XAMPP. In an illustrative case, SMART produced final scores of 0.6000 (Science), 0.4546 (Social Studies), and 0.4000 (Language), with manual and system calculations yielding identical results across all alternatives. Black box testing on 14 scenarios showed all system functions operated as expected. These results demonstrate that SMART can support objective preliminary major recommendations as a preparatory tool for guidance counselors rather than the final decision-maker, with validation on a broader student population identified as a direction for future research.